Pāratiyārin nakaiccuvaiyum naiyāṇṭiyum - Periaswamythooran, M. P., 1908- (Vāṉati Patippakam, 1980)
Humor and satire in the writings of C. Subrahmanya Bharati, 1882-1921, Tamil revolutionary poet; includes selections from his writings.